Optical regulation of endogenous RhoA reveals selection of cellular responses by signal amplitude - 주정민; 이해님; L Ning; 류현주; XX Zhou; 천혜연; 이용우; AI Lee-Richerson; 정철현; MZ Lin; Seong, Jihye (Cell Press, 2022)
How protein signaling networks respond to different input strengths is an important but poorly understood problem in cell biology. For example, RhoA can promote focal adhesion (FA) growth or disassembly, but how RhoA activity mediates these opposite outcomes is not clear. Here, we develop a photoswitchable RhoA guanine nucleotide exchange factor (GEF), psRhoGEF, to precisely control endogenous RhoA activity. Using this optical tool, we discover that peak FA disassembly selectively occurs upon activation of RhoA to submaximal levels. We also find that Src activation at FAs selectively occurs upon submaximal RhoA activation, identifying Src as an amplitude-dependent RhoA effector. Finally, a pharmacological Src inhibitor reverses the direction of the FA response to RhoA activation from disassembly to growth, demonstrating that Src functions to suppress FA growth upon RhoA activation. Thus, rheostatic control of RhoA activation by psRhoGEF reveals that cells can use signal amplitude to produce multiple responses to a single biochemical signal.